The IMPACT study: early loss of skeletal muscle mass in advanced pancreatic cancer patients. Issue 2 (4th February 2019) - Basile, Debora; Parnofiello, Annamaria; Vitale, Maria Grazia; Cortiula, Francesco; Gerratana, Lorenzo; Fanotto, Valentina; Lisanti, Camilla; Pelizzari, Giacomo; Ongaro, Elena; Bartoletti, Michele; Garattini, Silvio Ken; Andreotti, Victoria Josephine; et al.
Abstract: Background: Pancreatic cancer (PC) patients have multiple risk factors for sarcopenia and loss of skeletal muscle mass (LSMM), which may cause greater treatment toxicities, reduced response to cancer therapy, prolonged hospitalization, impaired quality of life, and worse prognosis. Methods: This is a retrospective study on advanced PC patients treated at the Department of Oncology of Udine, Italy, from January 2012 to November 2017. Among 162 patients who received chemotherapy, 94 consecutive patients with an available computed tomography (CT) scan were retrospectively analyzed. The primary objective of our study was to explore if an early LSMM ≥ 10% (measured at first radiological evaluation and compared with baseline) and/or baseline sarcopenia may impact prognosis. Baseline sarcopenia was defined according to Prado's criteria. Skeletal muscle area was measured as cross‐sectional areas (cm 2 ) using CT scan data through the Picture archiving and communication system (PACS) image system. Results: In the whole cohort, 48% of patients were ≤70 years old, and 50% had metastatic disease. At baseline, 73% of patients had sarcopenia, and 16% presented a visceral fat area ≥ 44 cm 2 /m 2 . Overall, 21% experienced an early LSMM ≥ 10%. Approximately 33% of sarcopenic patients at baseline and 35% of patients with early LSMM ≥ 10% had a body mass index > 25 kg/m 2 . Of note, 71% of patients were evaluated by a nutritionist, and 56% received a dietary supplementation (oral and/or parenteral). After a median follow‐up of 30.44 months, median overall survival (OS) was 11.28 months, whereas median progression‐free survival (PFS) was 5.72 months. By multivariate analysis, early LSMM ≥ 10% was significantly associated with worse OS [hazard ratio (HR): 2.16; 95% confidence interval (CI) 1.23–3.78; P = 0.007] and PFS (HR: 2.31; 95% CI 1.30–4.09; P = 0.004). Moreover, an exploratory analysis showed that inflammatory indexes, such as neutrophil–lymphocyte ratio variation, impact early LSMM ≥ 10% (odds ratio 1.31, 95% CI 1.06–1.61, P = 0.010). Conclusions: Early LSMM ≥ 10% has a negative prognostic role in advanced PC patients. Further prospective investigations are needed to confirm these preliminary data.